Energy economics : understanding energy security in China - Wei, Yi-Ming; Liang, Qiao-Mei; Wu, Gang; Liao, Hua (Emerald Publishing Limited, 2019)
As the largest energy consuming country and the second largest oil importing country, China has been the net importer of all fossil energy since 2009. With its increasing external energy dependence year by year, as well as frequent occurrences of oil, coal, and electricity shortages, the issue of energy security has been increasingly serious. What is the level of energy security in China? How might we improve national energy supply security and reduce energy trade risks? This book sets out a systematic piece of research which attempts to tackle these hot issues. It starts with the history of world energy geopolitics and domestic energy security, focusing on the hot issues of the complexity of the international energy market, and moves to domestic energy import trade risks, domestic strategic energy reserve strategies, and the impact of the energy crisis on domestic economy. Further insights include the environmental and health effects of energy consumption, the development potential of renewable energy, energy security early-warning and contingency plans, and an international comparison of energy security. The book will be an insightful resource for researchers and students of energy economics and energy management. It will also be a helpful support and reference tool for decision-makers in the energy industry.
Chapter 1. Review of world energy situation and China's energy security -- Chapter 2. World energy geopolitics development and China's energy diplomacy -- Chapter 3. Oil price and energy security -- Chapter 4. Assessment of energy import and transportation risk of China -- Chapter 5. Research on China's energy reserve strategy -- Chapter 6. Key provincial sectors for energy conservation in China -- Chapter 7. Effects of clean and renewable energy on national energy security -- Chapter 8. Energy poverty and energy use security -- Chapter 9. Energy supply crisis and economic security research -- Chapter 10. Energy consumption and public health in China -- Chapter 11. Comprehensive evaluation of national energy security -- Chapter 12. Challenges and outlook of China's energy security.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Energy security -- China; Energy policy -- China; Business & Economics -- Industries / Energy; Energy resources